Plants have two minds as we do - Tomonori Kawano; Yoshiaki Ushifusa; Stefano Mancuso; Frantisek Baluška; Lucia Sylvain-Bonfanti; Delphine Arbelet-Bonnin; François Bouteau (Plant Signaling & Behavior)
This discussion paper carefully analyzes the cognition-related theories proposed for behavioral economics, to expand the concepts from human behaviors to those of plants. Behavioral economists analyze the roles of the intuitive sense and the rational thoughts affecting the human behavior, by employing the psychology-based models such as Two Minds theory (TMT) highlighting intuitive rapid thoughts (System 1) and rational slower thoughts (System 2) and Prospect theory (PT) with probability (p)-weighting functions explaining the human tendencies to overrate the low p events and to underrate the high p events. There are similarities between non-consciously processed System 1 (of TMT) and overweighing of low-p events (as in PT) and also, between the consciously processed System 2 (of TMT) and underrating of high-p events (as in PT). While most known p-weighting mathematical models employed single functions, we propose a pair of Hill-type functions reflecting the collective behaviors of two types of automata corresponding to intuition (System 1) and rationality (System 2), as a metaphor to the natural light processing in layered plant leaves. Then, the model was applied to two different TMT/PT-related behaviors, namely, preference reversal and habituation. Furthermore, we highlight the behaviors of plants through the above conceptual frameworks implying that plants behave as if they have Two Minds. Lastly, the possible evolutionary origins of the nature of Two Minds are discussed.